A Preliminary Study on Light Transmittance Properties of Translucent Concrete Panels with Coarse Waste Glass Inclusions. (November 2015) - Pagliolico, Simonetta L.; Verso, Valerio R.M. Lo; Torta, Annalisa; Giraud, Maurizio; Canonico, Fulvio; Ligi, Laura
Abstract: This paper investigates the potential reuse of coarse glass wastes as insert in a high performance cement matrix to produce translucent concrete panels for architectural applications such as interior walls. The effects of the addition of glass scraps on chemical and optical properties of concrete were studied. Alkali-silica reactivity resistance tests were carried out to evaluate the reactivity between amorphous waste glass and alkaline concrete pore solution. Light transmittance LT was evaluated through Radiance simulations and measurements on sample prototypes. The increase in the amount of daylight in a sample room and the reduction in the energy demand for lighting EDl were investigated through Daysim simulations. Compared to two opaque side walls, the use of two translucent concrete walls with a LT of 5% allowed a reduction in EDl up to 16% in Palermo (L=38.3°N).